(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the performance of the process of decentralization of health surveillance actions in the State of Rio de Janeiro. Method: Evaluative research using mixed methods. First, documentary research was conducted on the process of decentralizing health surveillance in the State of Rio de Janeiro. In sequence, interrupted time series, a quasi-experimental method, was applied to test immediate and gradual effects of the intervention on the indicator “percentage of municipalities that carry out at least six groups of Health Surveillance actions considered necessary for all municipalities in the year”. This information was extracted from the Ambulatory Information System. In both approaches, the period of analysis comprised 2010 to 2019. Results: The timeline was essential to explain the path taken in the process of decentralization of health surveillance in the State, highlighting the main milestones, advances and challenges that emerged in this context. Segmented regression showed that from the expansion of intervention in the State there was an increase (β2) in the level of 5.12% (p = 0.0000) in the execution of the agreed actions. Over time, the trend (β3) showed decline of -8,39% (p = 0,1370). In the regions, the statistically significant increase in the level of the indicator was identified in the Baixada Litorânea (β2:19.90%, p = 0.0000 e IC 95%: 44.6582 – 55.1423), Médio Paraíba (β2:15.01%, p = 0.0000 e IC95%: 37.8740 – 52.1592), Serrana (β2:12.80%, p = 0.0000 e IC95%: 17.9140 – 22.1812), Metropolitanas I (β2: 37.82%, p= 0.0002 e IC95%: 28.5069 – 47.1460) e Metropolitana II (β2: 55.05%, p= 0.0011 e IC 95%: 43.2534 – 86.8552). Only the Serrana region showed a trend reduction of -10.63% statistically significant (p = 0.0000). Conclusion: The findings indicate that the process of decentralizing effective technical and administrative support to be legitimized in a social perspective aimed at promoting integrated actions.